THE ROLE OF LANGUAGE LEARNING KNOWLEDGE IN THE FORMATION OF WRITTEN SPEECH - Masharipova Nodira Raxmonovna (Scholar Express Journal, 2023)
The article presents some recommendations regarding the current issues facing mother tongue education and their solutions. Recommendations are given regarding the need to master language knowledge in the correct formation of written speech, problems in written speech and their solutions.
Keywords: Written speech; grammatical knowledge and understanding; literary standards